2020
DOI: 10.9734/ejnfs/2020/v12i430218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Citric Acid Treatment and Fermentation on the Chemical Composition of African Yam Bean (Sphenostylis stenocarpa) and Sensory Evaluation of Its Gruel

Abstract: Aims: Legumes, (especially indigenous/ underutilized legumes), have been found to make substantial contributions to nutrient intakes of the populace especially in low resources environments. The African yam bean (AYB) is one of such indigenous legumes with utilization constraints such as hard-to-cook phenomenon, beany flavour, bitter taste and some anti- nutritional factors that limit its utilization. The aims of this study were to determine effect of citric acid treatment and fermentation on the chemical comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This study recorded a significant increase (p<0.05) in the foaming capacity as the substitution with MKF and OPF varied increased from sample B to sample F. This could be due to the increase in protein content of the flours as MKF and OPF concentration increased. A similar trend was reported by Aburime et al, [24] and Chandra et al, [19].…”
Section: Functional Properties Of Wheat Orange Pomace and Mango Kerne...supporting
confidence: 90%
“…This study recorded a significant increase (p<0.05) in the foaming capacity as the substitution with MKF and OPF varied increased from sample B to sample F. This could be due to the increase in protein content of the flours as MKF and OPF concentration increased. A similar trend was reported by Aburime et al, [24] and Chandra et al, [19].…”
Section: Functional Properties Of Wheat Orange Pomace and Mango Kerne...supporting
confidence: 90%
“…The improved protein content in LAB and tsamiyan gaye (citric acid) fermented masa may indicate that fermenting masa with lactic acid bacteria (LAB) starter culture may improve it protein content as Olaoye, et al (2017) reported that lactic acid fermentation has been reported to contributes to the safety, health, organoleptic, technological and nutritional qualities of foods. Also Aburime et al (2020) reported that citric fermentation significantly increases the protein contents of foods due to low pH provided by the citric acid thus, facilitating solubilization of protein, resulting in higher protein yields. The crude fibre of the masa samples ranges from 0.37 -0.77% with starter culture fermented masa having highest value.…”
Section: Resultsmentioning
confidence: 99%
“…Effiong et al (2016) noted that an increase in the growth and proliferation of the fungi and bacteria complex in the form of single-cell proteins in 72 hours of cultured rumen digesta filtrate accounted for the apparent increase in the protein content of the I. manni meal. Aburime (2012) reported that fermentation of African yam bean (Sphenostylie stenocardia) in tap water for 24 hours and in lime water for 24 and 48 hours, caused a significant increase in the CP content from 24.19 to 33.08%. The increase in CP contents was also reported by following fermentation of Macrotermes nigeriensis, cassava and mahewu.…”
Section: Discussionmentioning
confidence: 99%